Existential protagonist in Naguib Mahfouz’s novel “The Beggar” - Naem, Ali Dakhil; Janoory, Lajiman Bin (International Journal of English Literature and Social Sciences (IJELS), 2019)
This study has the main objective that is, examining the concept of Existentialism in Naguib Mahfouz's novel "The Beggar". In it, Omer Al-Hamzawi, the protagonist of this novel, had chosen the death as an escape from the reality. Omer Al-Hamzawi was looking for the meaning of life and existence. This man who wants to evade his truth in search of new value renews the meaning he finds himself living a double he could not get rid of. This face of life did not die, but it is reflected in new images through the characters of the novel and confirms that the truth is ongoing and is pursued to the end. And Omar al-Hamzawi a goal sought to achieve. It is the "searching for the meaning of life." In order to achieve this lofty goal,the researcher has selected the topic that applies the existentialism to elucidate the burdens, hardships and the sense of being betrayed and disappointed with the values of the idealism, such betrayal and disappointment calls upon images and impressions of frustration and despair on the account of the Egyptians. Therefore, instances of the fictional works of Naguib Mahfouz would draw a fine and satisfactory picture of the plight of the modern man in an existential perspective that matches perfectly the theme of the study in content and medium of analysis. An analysis for this novel was conducted by the researcher who also reviewed relevant several books and journals and read the opinions and arguments of the critics in order to reveal how this Arab writer dealt with the death as a tool of escape. This study aims at examining the plight of the modern man due to multiple reasons like the effects of the two world wars, and being embedded to the colonial powers and the occupations of the small countries. Such big events have left a big stack on the shoulders of the regular citizens of the colonized countries. Particularly those countries with different ethics and moral codes.